HOMOGENEOUS CATALYSIS OF ELECTROCHEMICAL REACTIONS - MECHANISTIC RESOLUTION VIA ROTATING-DISK ELECTRODE VOLTAMMETRIC WAVESHAPE ANALYSIS - Compton, R; Spackman, R; Unwin, P (1989)
The shape of the current-voltage curves at a rotating disc electrode have been calculated for various nuances of the catalytic (EC') mechanism. In particular the halfwave potential is found to be highly sensitive to the disc rotation speed and the concentrations of mediator and substrate employed. These observations provide a ready method of characterising the different pathways. © 1989.